2022
DOI: 10.3390/nano12244408
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Diamane Nanostructures in Bilayer Graphene on Langasite under Irradiation with a Focused Electron Beam

Abstract: In the presented paper, we studied bilayer CVD graphene transferred to a langasite substrate and irradiated with a focused electron beam through a layer of polymethyl methacrylate (PMMA). Changes in the Raman spectra and an increase in the electrical resistance of bigraphene after irradiation indicate a local phase transition associated with graphene diamondization. The results are explained in the framework of the theory of a chemically induced phase transition of bilayer graphene to diamane, which can be ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Recently, the formation of diamane nanostructures in bilayer graphene on a La 3 Ga 5 SiO 14 substrate under focused electron beam irradiation was reported [18]. The observed results can be explained using the framework of the theory of a chemically induced phase transition from bilayer graphene to diamane [13].…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Recently, the formation of diamane nanostructures in bilayer graphene on a La 3 Ga 5 SiO 14 substrate under focused electron beam irradiation was reported [18]. The observed results can be explained using the framework of the theory of a chemically induced phase transition from bilayer graphene to diamane [13].…”
Section: Resultsmentioning
confidence: 86%
“…In recent research [18], the formation of diamondized regions in polymethyl methacrylate (PMMA)-covered bilayer graphene on the La 3 Ga 5 SiO 14 surface has been successfully demonstrated. In the investigation, two layers of graphene were transferred onto a langasite substrate and subjected to focused electron beam irradiation through a layer of polymethyl methacrylate.…”
Section: Introductionmentioning
confidence: 99%
“…It seems attractive to realize a controlled phase transition when local influence on the graphite structure induces its sp 3 -hybridization. Thus, previously it was shown that direct electron irradiation with a low energy of the hydrogenated carbon films allowed the formation of both isolated nanodiamond clusters [ 17 ] and 2D diamond areas [ 18 ]. It seems interesting to try to realize such an effect by the exposure to high-energy ions that allow for complete rearranging of the structure of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of such transformations include formation of carbon nanomembranes from monolayers of polycyclic aromatic molecules (with removal of hydrogen atoms by electron impacts), 9,10 cutting of carbon nanotubes by a nickel catalyst (with removal of carbon atoms from the catalyst by electron impacts) 11 and transition of bilayer graphene to the thinnest diamond film known as diamane (with supply of hydrogen atoms removed from the polymer layer by electron impacts). 12 In our recent work, 13 we proposed the general strategy of synthesis of new carbon nanoobjects via hydrogen removal by electron irradiation in HRTEM followed by spontaneous transformation of precursor macromolecules which become unstable or metastable without hydrogen. For this approach, the kinetic energy of electrons in HRTEM should be sufficient to remove hydrogen but insufficient to damage the precursor backbone.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of such transformations include formation of carbon nanomembranes from monolayers of polycyclic aromatic molecules (with removal of hydrogen atoms by electron impacts), 9,10 cutting of carbon nanotubes by a nickel catalyst (with removal of carbon atoms from the catalyst by electron impacts) 11 and transition of bilayer graphene to the thinnest diamond film known as diamane (with supply of hydrogen atoms removed from the polymer layer by electron impacts). 12…”
Section: Introductionmentioning
confidence: 99%